Esotropia in Children with Ventricular-Peritoneal Shunts. (3rd July 2015) - DeBenedictis, Caroline N.; Rubin, Steven E.; Kodsi, Sylvia R.
ABSTRACT: Purpose : Compared with the general population, patients with hydrocephalus are more likely to have strabismus. This study was undertaken to examine characteristics and outcomes of children with esotropia and ventricular-peritoneal shunt placement due to hydrocephalus. Methods : This is a retrospective chart review of all pediatric patients with esotropia and a history of ventricular-peritoneal shunt placement seen by our pediatric ophthalmology service between January 2000 and December 2010. Results : Sixteen patients between the age of 3 months and 5.6 years met study criteria. Nine were premature and all but one of the patients had developmental delay. Although all patients had a ventricular-peritoneal shunt, the diagnosis leading to shunt placement was intraventricular hemorrhage or congenital hydrocephalus in 75% of the patients. In all but 3 patients the hydrocephalus was diagnosed before the esotropia. Ten children had congenital esotropia and 6 had acquired esotropia. Eleven of the 16 children required glasses: 5 had a myopic prescription and 6 had a hyperopic prescription. Treatment of the esotropia resulted in 9 patients (56%) with successful ocular alignment (<10 prism diopters) on their last visit: 7 underwent strabismus surgery and 2 were treated with glasses only. Of the 9 patients who had strabismus surgery, 6 had congenital esotropia and 3 had acquired esotropia. Among patients who underwent strabismus surgery, 78% had successful ocular alignment at their last visit. Conclusions : While acquired accommodative esotropia is more common in the general population, children with ventricular-peritoneal shunts may be more likely to have congenital esotropia. Although developmental delay is very frequent, successful ocular alignment may be possible in this patient population.